Supply and demand in the training of quantum software engineering workforce - Aparicio-Morales, Álvaro M. (2024)
Quantum Technologies are experiencing significant growth due to substantial investments made by governments worldwide. These investments aim to enhance global competitiveness in this field and position countries as key players. However, facing the changes of this new paradigm requires an increment in the workforce with specialized expertise in Quantum Technologies, particularly in the area of Quantum Computing. In this paper, we present a concise overview of the current quantum computing education offers and an outline of the current job offer landscape. We highlight essential elements for individuals interested in building a career profile in quantum software engineering, including understanding the professional requirements that experts and companies have established. The main goal of this paper is to offer an overview of the current educational and professional landscape in the quantum software engineering field, empowering the next generation of software engineers to thrive in a quantum technologydriven future that will profoundly impact human lives.